Governance for Learning Outcomes in European Policy-Making: Qualification Frameworks Pushed through the Open Method of Coordination - Odd Bjørn Ure (International Journal for Research in Vocational Education and Training (IJRVET), 2015)
The construction of European education policy builds on a widely shared goal of transparency in qualifications, upheld by the popular narrative of mobile students endowed with scholarships from the EU Erasmus programme, which~ allow them~ to transfer credit points between universities and across national borders. EU education policy is increasingly inscribed in National Qualification Frameworks (NQF). Their European umbrella is coined~ the European Qualification Framework (EQF), which is linked to a discourse on or even shift to Learning Outcomes; functioning as~ a tool for the displacement of input to output categories in education systems with a view to make qualifications more transparent. This form of governance situates Learning Outcomes as a tool for policy reform that intentionally should affect all educational and administrative levels of European education. The article shows that the multitude of governance instruments used to promote a shift to Learning Outcomes are so varied that EU education policy has no apparent need of new instruments for this purpose. The fact that Learning Outcomes are linked to EU policy instruments of the Open Method of policy-Coordination and destined for several sectors of education, increases the likelihood that they will be translated into modified learning practices. Yet, there is a danger that governance of Learning Outcomes succumbs to a pitfall of declaratorily placing Learning Outcomes in the middle of learning practices in all subsectors of education, without sufficiently proving their real novelty and regulatory functions.
Keywords: 330; Qualifications Frameworks; EU Policy Coordination; Learning Outcomes; Governance; Knowledge Production